A Discussion of Josiah Ober's The Rise and Fall of Classical Greece. Issue 4 (28th December 2016) - Acemoglu, Daron; Robinson, James A.; Weingast, Barry R.
Abstract : Ancient Greece has long exercised a powerful hold on the imagination of modern political science. But until fairly recently, this influence has largely been philosophical, related to the origins of many theoretical concepts—including the concept of politics itself—in the ancient world. In The Rise and Fall of Classical Greece, Josiah Ober offers a synoptic and ambitious social theoretical account of the ancient Greek world, the sources of its power, the causes of its decline, and the lessons that can be drawn from this story for contemporary social and political science. We have thus invited a range of political scientists to comment on Ober's account of classical Greece and its relevance to contemporary political inquiry.